ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI KABUPATEN TANGERANG PADA TAHUN 2009 – 2015 - Karnawi Kamar (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
This study aimed to analyze the effect of economic growth and investment in the labor market in the Tangerang regency in the year 2009-2015.This research is quantitative descriptive research design and associative. The data used are time series data of economic growth, investment and employment in the Central Statistics Agency (BPS) 2009-2015 Tangerang regency. Data collection techniques are documentation in the form of books, journals and reports. Data were analyzed using descriptive statistics, the classic assumption test, simple and multiple correlation, coefficient determination test, regression test and the partial hypothesis test (t test) and simultan hypotheses test (F test) with the help of SPSS software.The analysis showed partial negative effect on economic growth or reverse direction and no significant effect on employment. Simultaneously, economic growth and the positive impact of investment direction and significant increases on employment. Keywords: Economic Growth, Investment, Labor Absorption